KECERDASAN SPIRITUAL: PENGARUHNYA TERHADAP KESADARAN MORAL MAHASISWA DALAM PEMANFAATAN KECERDASAN BUATAN DI ERA DIGITAL - Salsabila Ariyani; Istihana Istihana; Sunarto Sunarto; Baharudin Baharudin (Jurnal Bilqolam Pendidikan Islam, 2025)
This study is motivated by the phenomenon of low moral awareness among students in using artificial intelligence, despite the fact that some of them possess a high level of spiritual quotient. This condition raises the question of whether spiritual intelligence is truly related to moral awareness in the digital era. The purpose of this research is to analyze the relationship between spiritual quotient (SQ) and students’ moral awareness in the use of AI. The study employs a quantitative approach with a correlational design. The sample consisted of 30 Islamic Education students at UIN Raden Intan Lampung, selected through a simple random sampling technique. The instrument, in the form of a five-point Likert scale questionnaire, was tested for validity, reliability, and prerequisite analyses including normality, homogeneity, and linearity, and subsequently analyzed using the Mann–Whitney test, t-test, F-test, and coefficient of determination. The findings reveal that there is no significant relationship between SQ and moral awareness; spiritual intelligence does not influence moral responsibility in the use of AI (sig. 0.986). This indicates a gap between students’ internal spirituality and their digital moral behavior. In conclusion, fostering digital morality cannot rely solely on strengthening SQ, but requires AI ethics literacy, self-regulation, and a supportive academic culture. This study contributes theoretically to the discourse on digital morality and highlights the importance of integrating spiritual values with technological ethics in higher education